FUNCTIONAL PROPERTIES OF CENTELLA ASIATICA (L.): A REVIEW - Vasantharuba, S.; Sundaram, S.P.; Arumugam, T.; Banumathi, P.; Premalatha, M.R. (My University, 2012)
Centella asiatica (L.) is a perennial, creeper, faintly aromatic and a valuable medicinal herb of both old world and the new world. It is widely distributed throughout tropical and subtropical regions of World. The use of Centella in food and beverages has increased over the years basically due to its beneficial functional properties. Its potential antioxidant, antimicrobial, cytotoxic, neuroprotective and other activities have been widely claimed in many reports and basically is very much related to its properties and mechanism of action of the plant’s bioactive constituents namely the triterpinic acid (asiatic acid and madecassic acid) triterpinic saponin (madecassoside andasiaticoside), flavonoids and other phenolic compounds. The present review is an up-to-date and comprehensive literature analysis of the chemistry and various heath beneficial functional properties of the Centella plant.
Keywords: Centella asiatica; Functional properties; Bioactive constituents; Health benefits